Reexamination of the Curator’s Authority in Convening a General Meeting of Shareholders (GMS) for the Liquidation Bankrupt Estate Assets - Jo Wendy Suyoto; Waty Suwarty Haryono; Yuherman Yuherman; Saefullah Saefullah (International Journal of Social Service and Research, 2026)
This study examines the authority of the curator in convening or facilitating a General Meeting of Shareholders (GMS) in a Limited Liability Company (LLC) declared bankrupt, with a particular focus on the curator’s role in the settlement of the bankrupt estate. This research employed a normative juridical approach using statutory, case, and conceptual approaches, with secondary legal materials obtained through library research. Three core issues were analyzed: first, the normative conflict between bankruptcy law (Law No. 37 of 2004) and company law (Law No. 40 of 2007) concerning the position of the GMS in bankrupt LLCs; second, the appropriate legal construction for addressing the normative gap regarding the curator’s authority to convene a GMS based on authority theory and the principle of legal certainty; and third, a future model for the curator’s authority in implementing a GMS for the settlement of bankrupt estate assets. The findings reveal the existence of a normative conflict and legal vacuum regarding the relationship between the curator’s authority and the GMS in bankrupt LLCs, resulting in legal uncertainty in practice. This study proposes a legal reconstruction model that positions the curator as the party authorized to convene a GMS under specific circumstances related to the settlement of bankrupt estate assets, subject to approval from the supervisory judge and compliance with the GMS mechanisms established under company law. It concludes that reconstructing the curator’s authority through harmonization between Law No. 37 of 2004 and Law No. 40 of 2007 is necessary to achieve legal certainty, strengthen creditor protection, and ensure the effective settlement of bankrupt estate assets.